2016
DOI: 10.1111/bcpt.12644
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Bupivacaine after Administration of a Lozenge as Topical Treatment for Pain from Oral Mucositis

Abstract: Abstract:The aim was to investigate systemic exposure after administration of a novel bupivacaine lozenge in healthy individuals with normal mucosa and in head and neck cancer (HNC) patients with oral mucositis. A lozenge containing 5, 10, 25 and 50 mg bupivacaine, respectively, was administered as single dose to 10 healthy individuals, and a lozenge containing 25 mg bupivacaine was administered as single dose to 10 HNC patients with oral mucositis and as multiple doses to five patients with HNC. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Method and results of these data on the 10 patients are reported in the study by Mogensen et al, 2017. 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Method and results of these data on the 10 patients are reported in the study by Mogensen et al, 2017. 10 …”
Section: Methodsmentioning
confidence: 99%
“…They showed no signs of toxic plasma concentrations or risk of aspiration. 10 , 11 Moreover, a pilot study in which a single dose of the lozenge was administered to patients with head and neck cancer showed a strong, long-lasting pain-relieving effect, with a mean duration of maximum pain relief in the oral cavity of 42 minutes and a significant pain relief even after 180 minutes. 12 Lidocaine viscous solution has been reported to have a duration of 15 to 20 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Oral mucositis is a side effect of azathioprine therapy . In patients with oral mucositis, bupivacaine absorption from lozenges was increased and a trend to higher fentanyl absorption administered with a sublingual spray was observed but did not reach statistical significance . The effect may be due to impairment of the barrier function of the mucosa.…”
Section: Medicines Used To Treat Gastrointestinal Diseases and Their mentioning
confidence: 99%
“…In these studies, absorption of bupivacaine and the risk of aspiration were investigated and no toxic plasma concentrations or signs of aspiration were observed, whereas the results indicated that a bupivacaine lozenge is safe to use. 14 , 15…”
Section: Introductionmentioning
confidence: 99%